Porous Electrospun Fibers Embedding TiO2 for Adsorption and Photocatalytic Degradation of Water Pollutants - Lee, Chang Gu; Javed, Hassan; Zhang, Danning; Kim, Jae Hong; Westerhoff, Paul; Li, Qilin; Alvarez, Pedro J.J. (Environmental Science and Technology, 2018)
Using a bipolymer system consisting of polyvinylpyrrolidone (PVP) and poly(vinylidene fluoride) (PVDF), P25-TiO2 was immobilized into thin film mats of porous electrospun fibers. Pores were introduced by dissolving sacrificial PVP to increase surface area and enhance access to TiO2. The highest photocatalytic activity was achieved using a PVDF:PVP weight ratio of 2:1. Methylene blue (MB) was used to visualize contaminant removal, assess the sorption capacity (5.93 ± 0.23 mg/g) and demonstrate stable removal kinetics (kMB > 0.045 min-1) under UVA irradiation (3.64 × 10-9 einstein/cm2/s) over 10 cycles. Treatment was also accomplished via sequential MB sorption in the dark and subsequent photocatalytic degradation under UVA irradiation, to illustrate that these processes could be uncoupled to overcome limited light penetration. The photocatalytic mat degraded bisphenol A and 17α-ethynylestradiol in secondary wastewater effluent (17 mg TOC/L), and (relative to TiO2 slurry) immobilization of TiO2 in the mat mitigated performance inhibition by co-occurring organics that scavenge oxidation capacity. This significantly lowered the electrical energy-per-order of reaction (EEO) needed to remove such endocrine disruptors in the presence of oxidant scavenging/inhibitory organics. Thus, effective TiO2 immobilization into polymers with affinity toward specific priority pollutants could both increase the efficiency and reduce energy requirements of photocatalytic water treatment.
Keywords: Contaminant removal; Electrical energy per order; Photo catalytic degradation; Photocatalytic activities; Photocatalytic water treatment; Poly (vinylidene fluoride)(PVDF); Polyvinyl pyrrolidone; Wastewater effluents; Adsorption; Catalysis; Porosity; Titanium; Water Pollutants; Water Pollutants, Chemical